Desarrollo de un software para la evaluación de riesgos de la seguridad informática basado en la norma ISO 27001:2005, para su aplicación en la cátedra de auditoría de sistemas en el instituto superior tecnológico particular Latinoamericano - Sánchez Mendieta, Hernán Mauricio (2013)
In this thesis a tool to expedite the process of risk assessment of information security based on the standard ISO 27001: 2005 is provided, which seeks to improve the standard management processes Internal Audit of enterprises and provide security to information, as a means to train students "Latin American" in the chair of Systems Audit particularly Technical Institute.